PROMOTING ENVIRONMENTALLY FRIENDLY BEHAVIOR THROUGH GREEN ECONOMY-BASED ENGLISH LEARNING AT AL WASHLIYAH UNIVERSITY MEDAN - Rambe, Shopiah Anggraini; Ayla, Sri (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
This study explores the impact of green economy-based English language learning on environmental awareness among students at Al Washliyah University Medan. Recognizing the role of education in addressing global environmental challenges, the research aims to assess how incorporating green economy principles into English learning influences students' attitudes and behaviors towards sustainability. The study employs a sample of 32 students and uses multiple linear regression analysis to examine the effects of promotion and environmentally friendly behavior on English language learning. Results show that while promotion does not significantly affect English learning, eco-friendly behavior has a substantial positive influence. Together, promotion and eco-friendly behavior account for 65.2% of the variance in English learning based on the green economy. The findings underscore the potential of integrating green economy concepts into educational curricula to promote environmental awareness and foster sustainable behaviors in higher education.